Feasibility and acceptability of a mobile model of environmental enrichment for patients with mixed medical conditions receiving inpatient rehabilitation: a mixed methods study. Issue 9 (17th September 2022) - Fulton, Sarah; Janssen, Heidi; Salih, Salih; James, Alecia; Elphinston, Rachel A
Abstract : Objectives: To investigate the feasibility and acceptability of a mobile model of environmental enrichment (EE), a paradigm that promotes activity engagement after stroke, in patients with mixed medical conditions receiving inpatient rehabilitation. Design: A mixed methods study design was used. An online qualitative survey assessed staff perspectives of acceptability of the mobile EE model including perceived barriers and enablers pre-implementation and post implementation. An A-B quasi-experimental case study of patient activity levels over a 2-week observational period provided feasibility data. This included recruitment and retention rates, completion of scheduled patient activity observations and validated baseline questionnaires, and number of adverse events. Setting: A 30-bed mixed medical ward in a public hospital that services Brisbane's southern bayside suburbs. The rehabilitation programme operates with patients co-located throughout the medical/surgical wards. Participants: Nursing and allied health professionals working across the rehabilitation programme completed pre-implementation (n=19) and post implementation (n=16) qualitative questions. Patients admitted to the ward and who received the inpatient rehabilitation programme from June to November 2016 were also recruited. Interventions: The mobile EE intervention included activities to primarily promote social and cognitive stimulation (eg, puzzles, board games) delivered by hospital volunteers and was designed to be moved throughout the wards. Results: Four themes emerged from staff reports, suggesting that the role of patient, staff and intervention characteristics, and the ward environment were important barriers and enablers to implementation. Of the 12 eligible patients, six consented to the study, and five completed the intervention. All patients completed the baseline measures. No adverse events were reported. Conclusions: As interest grows in human EE models, it will be important to tailor EE interventions to the unique demands of hospital rehabilitation services. A mobile EE model delivered in a small, mixed rehabilitation ward appears feasible and acceptable to study in a larger controlled feasibility trial.